Perfil lipídico convencional e não convencional em idosos com doença de Alzheimer - Claudia Bandeira de Melo Franca (2011)
Alzheimer's disease (AD) is the most prevalent formof dementia, common among the elderly worldwide. With an estimated prevalence of 7% in the Brazilian elderly population,, it has aging is the major risk factor for AD. Other factors are associated with low education and low occupational demand, reduced physical and mental activities, brain trauma and factors associated with vascular disease such as hypercholesterolemia, hypertension, atherosclerosis, coronary disease, smoking, obesity and diabetes.As the DA is a multifactorial and a chronic degenerative disease the hypothesis of this study is that changes in lipid profile of patients with this disease may be risk factors. Thus, this study aims to characterize the population with AD, compared to those without the disease, with regard to lipid profile, including the determination of both the conventional (total and fractionated cholesterol and triglycerides) and non conventional lipid profiles [apolipoproteins A-I and B, and lipoprotein (a)]. The study included 49 patients with AD selected from the outpatient clinic of the Institute of Jenny Andrade Faria, Hospital das Clinicas, UFMG, whose diagnosis was defined by applying a standardized protocol and multi-dimensional assessment of the elderly, prepared by the Reference Center for the Elderly Prof. Benjamin Caio Dias-UFMG Hospital das Clínicas. For comparison there were also studied 40 subjects without AD, with age, education and socioeconomic status similar to patients with AD recruited from SESC - Social Service of Commerce, which underwent clinical multidimensionalevaluation and three screening instruments (Mini-mental state, Category fluency test, Clock Drawing Test), to exclude the diagnosis of AD. Blood samples were obtained from all participants for the determination of plasma APOA-I, APOB and Lp(a) as well as for determining the conventional lipid profile. Contrary to expectation, for the conventional lipidprofile, it was observed a statistically significant difference related to TC, TG and VLDL, whose plasma levels were higher in the group without the disease when compared to the group with AD. However, with regard to non conventional lipid profile, including plasma levelsof APOA-I, APOB and Lp(a), no significant difference was observed between groups with AD and without the disease. As the study sample was small, the importance of changes in the conventional and non conventional lipid profiles in the genesis of the Alzheimer disease cannot be rule out.